The Effect of Plyometric Training up and downstairs and obstacle jumping on the improvement of squat style long jump results for male participants in the DKI Jakarta Athletic Club - Mohammd Fathan Mubina; Moch. Asmawi; Heny Widyaningsih (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
The objectives of this study were 1) To improve the hurdle jumping training on the long jump results of the squat style in the male participants of the DKI Jakarta club. 2) Increasing the plyometric training up and downstairs to the results of the squat-style long jump in the male participants of the DKI Jakarta club. 3) This is more influential between the plyometric training of hurdle jumping and plyometric training up and downstairs to improve the squat style long jump results for male participants in the DKI Jakarta club. The method to be used is an experimental method, namely the research design using